Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution

Promising visible-light driven hydrogen production from water on a highly efficient CuCo2S4 nanosheet photocatalyst - Chauhan, Meenakshi; Soni, Kiran; Karthik, P. E.; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2019)
Here we report the development of CuCo2S4 nanosheets (NSs) as a promising semiconductor photocatalyst for the first time for water splitting reactions under visible light ( 420 nm) conditions, without the support of any noble metal co-catalyst. These NSs were produced via a simple hydrothermal route and have desirable properties with a band gap of 2.24 eV, and are photo-catalytically active under visible light with an apparent quantum yield (AQY) of 2.48%. Under visible light, CuCo2S4 NSs exhibit excellent weight-normalized photoactivity that generates approximate to 25900 mol h(-1) H-2 for 1 g of material with sulphide + sulphite as the sacrificial agent under 7.68 mW cm(-2) illumination, which is the best evolution reported for any chalcogenide semiconductor material without any co-catalyst to date with unprecedented long-term operational stability (up to 12 h study time). The rate and number of hydrogen gas molecules produced are 8.2855 x 10(15) s(-1) cm(-2) which remained constant for three catalytic cycles with a turnover frequency (TOF) value of 0.017 s(-1). The effect of Cu substitution on photoactivity was also investigated for comparative studies and it was found that CuCo2S4 NSs show superior activity to Cu0.5Co2.5S4 and Co3S4. These CuCo2S4 NSs absorb the entire visible range of the spectrum from 420 to 800 nm, and have a highly populated density of states at the Fermi level and a high donor concentration of 7.22 x 10(18) cm(-3) which have been evaluated by Mott-Schottky analysis and favourable adsorption of H+ on S-sites and conversion to H-2 corroborate their efficient photocatalytic activity.